2019
DOI: 10.3221/igf-esis.49.67
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of thermomechanical behavior of acrylonitrile butadiene styrene using a newly developed nonlinear damage-reliability model

Abstract: The aim of this work was to evaluate the influence of temperature on the mechanical behavior of an amorphous polymer, namely acrylonitrile butadiene styrene (ABS), based on a series of uniaxial tensile tests on smooth specimens at different temperatures. The results demonstrate that the behavior of the polymers is strongly dependent on the temperature. Its influence on the physical characteristics during the study of polymer behaviors cannot be denied, particularly when the processes of shaping are investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Fig. 11 demonstrates the evolution of experimental damage based on ultimate stress in function according to life fraction β [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Experimental Damagementioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 11 demonstrates the evolution of experimental damage based on ultimate stress in function according to life fraction β [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Experimental Damagementioning
confidence: 99%
“…En-naji et al, examined the properties of ABS polymer plate subjected to uniaxial loading. The authors employed a standardized damage model to characterize the underlying mechanical behavior of the plate [14]. Plaseied and Fatemi examined the effects of strain rate and temperature on the tensile properties of a vinyl ester polymer.…”
Section: Introductionmentioning
confidence: 99%
“…This expression will be exploited to evaluate the damage in the ABS and to give a benchmark of comparison between the present theory and the experimental results. The loss rate is presented by the following mathematical expression [18]:…”
Section: Key Engineering Materials Vol 820 -Loss Of Ultimate Stressmentioning
confidence: 99%
“…The static flow based on ultimate stress, has been developed to predict the flow evolution of the polymer in high temperature (T>Tg). The static flow model is presented in the equation ( 5) [18]. It is noted that the flow curves approaches gradually the bisector (the linear Miner Law) versus β' for high levels of loading.…”
Section: Quantification Of Static Flowmentioning
confidence: 99%
“…However, some experts are intrigued by this situation and are interested in exploring the effects of notches. This aspect of the research was pursued by I. Makadir et al [6] and A. Ennaji et al [7] They conducted tensile tests on specimens with induced damage and observed that the single notched specimen exhibited the highest level of brittleness. Among all the defects, the single notched defect exhibited the highest criticality.…”
Section: Introductionmentioning
confidence: 99%